Composite structure and method for manufacturing the same
Patent Information
- Application Number
- JP2023138806
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本開示によれば、熱伝導率に優れる樹脂金属複合構造体及びその製造方法を提供することができる。
Smart Images

Figure 2025033233000001 
Figure 2025033233000002 
Figure 2025033233000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite structure formed by bonding a metal member and a molded article obtained by melt molding a polyarylene sulfide resin composition, and a method for producing the same. [Background technology]
[0002] In recent years, with technological developments such as miniaturization and high output of semiconductor chips, the increase in the amount of heat generated by semiconductors has become an issue. In order to maintain the function of a semiconductor, it is necessary to improve the heat dissipation efficiency of the semiconductor substrate, and heat dissipation is generally improved by connecting it to a heat sink or the like. In order to improve the heat dissipation of a semiconductor using such a heat sink, the issues are to reduce the thermal resistance of the semiconductor chip itself and the thermal resistance of the heat sink, and to reduce the thermal conduction resistance of the contact interface between the semiconductor and the heat sink. In the conventional technology, for example, a grease or sheet with high adhesion and high thermal conductivity is placed between the semiconductor substrate and the heat sink to improve the heat dissipation of the semiconductor, but the use of the grease or sheet has the problem of being complicated in that it requires a coating process and a placement process.
[0003] On the other hand, thermoplastic resin materials are increasingly being used as materials for forming the substrates and housings that come into contact with semiconductors, due to their high production efficiency and high degree of freedom in moldable shapes. Polyarylene sulfide (PAS) resin, typified by polyphenylene sulfide (PPS) resin, is one of the resins often used for this purpose, due to its excellent mechanical strength, heat resistance, chemical resistance, moldability, dimensional stability, and flame retardancy. A commonly used technique for reducing the thermal resistance of molded products made of PAS resin is to increase the thermal conductivity of the material by filling it with a high ratio of fillers with high thermal conductivity.
[0004] For example, Patent Document 1 discloses a resin composition consisting of 10-60% by weight of a resin such as PPS and 40-90% by weight of graphite having a particle size of 20-900 μm (the sum of the two is 100% by weight). Patent Document 2 discloses a highly thermally conductive resin composition obtained by blending 100 parts by weight of PAS resin and 80-600 parts by weight of magnesium oxide that has been surface-treated in advance with a vinylalkoxysilane compound. Patent Document 3 discloses a resin composition containing 5-50 parts by weight of graphite, 5-80 parts by weight of talc, and 5-80 parts by weight of glass fiber relative to 100 parts by weight of PAS resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-339290 A [Patent Document 2] International Publication No. 2013 / 161844 Brochure [Patent Document 3] JP 2022-160098 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, materials that are highly filled with a filler having high thermal conductivity have low fluidity during molding and a fast solidification speed, so that the resin component cannot follow the mold surface during injection molding, and there is a problem that it is difficult to obtain a smooth surface. Therefore, when a resin molded product with an uneven surface is stacked on a metal heat sink or other part, an air layer with low thermal conductivity is formed on the uneven surface of the resin molded product, making it difficult to obtain a composite structure of a resin material and a metal material with high heat dissipation. However, none of the above documents discloses the surface smoothness of the PPS resin composition.
[0007] Therefore, an object of the present disclosure is to provide a resin-metal composite structure having excellent thermal conductivity and a method for producing the same. [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the present inventors have discovered that by controlling the developed area ratio (Sdr) of the surface of a resin member used in a composite structure to a specific value, it is possible to further improve adhesion to a metal member and reduce loss in thermal conduction efficiency at the interface between the resin member and the metal member, and have thus completed the present disclosure.
[0009] That is, the present disclosure relates to a composite structure in which a metal member and a resin member made of a molded product obtained by melt molding a PAS resin composition containing a PAS resin are joined together, The thermal conductivity of the resin composition in the thickness direction is 0.65 W / m K or more, and The composite structure has a number average developed area ratio (Sdr) of 0.03% or less when any five points on the resin member are measured using a confocal microscope in accordance with ISO 25178.
[0010] The present disclosure also provides a method for producing a composite structure, the method comprising the step of joining a metal member and a resin member made of a molded product obtained by melt molding a PAS resin composition containing a PAS resin, the method comprising the steps of: The thermal conductivity of the resin composition in the thickness direction is 0.65 W / m K or more, and The method for producing a composite structure, wherein the number average developed area ratio (Sdr) is 0.03% or less when any five points of the resin member are measured using a confocal microscope in accordance with ISO 25178. Effect of the Invention
[0011] According to the present disclosure, it is possible to provide a resin-metal composite structure having excellent thermal conductivity and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present disclosure will be described in detail, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made without departing from the spirit of the present disclosure. In addition, when multiple upper and lower limit values are described for a specific parameter, any upper and lower limit values can be combined to form a suitable numerical range.
[0013] The composite structure according to the present embodiment is a composite structure in which a metal member and a resin member made of a molded product obtained by melt molding a PAS resin composition containing a PAS resin are joined together, The thermal conductivity of the resin composition in the thickness direction is 0.65 W / m K or more, and The resin workpiece is characterized in that the number average developed area ratio (Sdr) is 0.03% or less when any five points on the resin workpiece are measured using a confocal microscope in accordance with ISO 25178. The following will explain this.
[0014] <Metal parts> The composite structure according to the present embodiment includes a metal member. The metal member that can be applied to the present embodiment is not particularly limited as long as it does not impair the effects of the present invention, and any known metal member can be used. For example, aluminum, copper, magnesium, iron, titanium, or an alloy containing them can be used. More specifically, examples of the alloy include iron and, for example, stainless steel and steel, which are mainly composed of iron, i.e., 20% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass, and further contain carbon, silicon, manganese, chromium, tungsten, molybdenum, phosphorus, titanium, vanadium, nickel, zirconium, boron, etc. (hereinafter, iron alloy); aluminum and an alloy having aluminum as the main component and containing copper, manganese, silicon, magnesium, zinc, nickel, etc. (hereinafter, aluminum alloy); magnesium and an alloy having magnesium as the main component and containing zinc, aluminum, zirconium, etc. (hereinafter, magnesium alloy); copper and an alloy having copper as the main component and containing zinc, tin, phosphorus, nickel, magnesium, silicon, chromium, etc. (hereinafter, copper alloy); and titanium and an alloy having titanium as the main component and containing copper, manganese, silicon, magnesium, zinc, nickel, etc. (hereinafter, titanium alloy). Among these, iron, iron alloys, aluminum alloys, magnesium alloys, copper alloys, and titanium alloys are more preferable, and iron alloys, aluminum alloys, and magnesium alloys are further preferable.
[0015] The shape of the metal member is not particularly limited, and examples of the shape include those processed into, for example, a flat plate, a curved plate, a rod, a cylinder, a block, a sheet, etc., by plastic processing such as pressing, punching, cutting, polishing, and thinning processing such as electric discharge processing. In addition, it may be a film-like object such as a metal foil.
[0016] The metal member may have a smoothed surface. A known method for smoothing the surface may be used, such as (1) mechanical polishing, (2) electrolytic polishing, or (3) chemical polishing. Of these, (1) mechanical polishing or (2) electrolytic polishing is particularly preferred as a method for smoothing the surface of the metal member. When smoothing the metal member, it is preferred to process the metal member into a predetermined shape by cutting, plastic processing such as pressing, punching, cutting, grinding, or thinning such as electric discharge processing before forming the above-mentioned smooth surface. When smoothing the metal member, from the viewpoint of thermal conduction with the resin molded product, the surface line roughness Rz is preferably 3.0 μm or less, more preferably less than 3.0 μm, and even more preferably 2.8 μm or less. The surface line roughness Rz of the metal member can be measured by the method described in the Examples in accordance with JIS-B 0601-2001 (ISO4287).
[0017] A primer layer may be formed on the surface of the metal member that has been subjected to the metal smoothing treatment. The material constituting the primer layer is not particularly limited, but is usually made of a primer resin material containing a resin component. The primer resin material is not particularly limited, and a known material can be used. Specifically, known polyolefin-based primers, epoxy-based primers, urethane-based primers, etc. can be mentioned. The method of forming the primer layer is not particularly limited, but for example, the solution of the above-mentioned primer resin material or the emulsion of the above-mentioned primer resin material can be applied to the metal member that has been subjected to the above-mentioned surface treatment to form the primer layer. Examples of the solvent used to prepare the solution include toluene, methyl ethyl ketone (MEK), and dimethyl phosphoramide (DMF). Examples of the medium for the emulsion include an aliphatic hydrocarbon medium and water. When forming the primer layer, the surface line roughness Rz is preferably 3.0 μm or less, more preferably less than 3.0 μm, and even more preferably 2.8 μm or less.
[0018] <Resin materials> The composite structure according to the present embodiment uses a resin member made of a molded product obtained by melt molding a PAS resin composition containing a PAS resin. First, the PAS resin composition containing a PAS resin, which is one of the components of the resin member, will be described.
[0019] [Resin composition] The PAS resin composition used in the present embodiment is prepared by melt-kneading a PAS resin as an essential component and, if necessary, blending other components.
[0020] ·PAS resin The PAS resin has a resin structure having a repeating unit in which an aromatic ring and a sulfur atom are bonded, and specifically, the PAS resin is represented by the following general formula (1):
[0021] [ka] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group.
[0022] [ka] The trifunctional structural moiety represented by formula (2) is preferably present in an amount of 0.001 to 3 mol %, particularly preferably 0.01 to 1 mol %, based on the total number of moles of the trifunctional structural moiety and other structural moieties.
[0023] Here, the structural portion represented by the general formula (1) is particularly R 1 and R 2 is preferably a hydrogen atom from the viewpoint of the mechanical strength of the PAS resin, and in that case, examples include those bonded at the para position represented by the following formula (3) and those bonded at the meta position represented by the following formula (4).
[0024] [ka] Among these, a structure in which the bond between the sulfur atom and the aromatic ring in the repeating unit is at the para position represented by the general formula (3) is particularly preferred in terms of the heat resistance and crystallinity of the PAS resin.
[0025] The PAS resin may include not only the structural moieties represented by the general formula (1) or (2) but also the structural moieties represented by the following structural formulae (5) to (8):
[0026] [ka] The structural moieties represented by the general formulae (1) and (2) may account for 30 mol % or less of the total of the structural moieties represented by the general formulae (1) and (2). In particular, in the present disclosure, it is preferable that the structural moieties represented by the general formulae (5) to (8) account for 10 mol % or less in terms of the heat resistance and mechanical strength of the PAS resin. When the PAS resin contains the structural moieties represented by the general formulae (5) to (8), the bonding mode thereof may be either a random copolymer or a block copolymer.
[0027] The PAS resin may have naphthyl sulfide bonds or the like in its molecular structure, but the amount of such bonds is preferably 3 mol % or less, and particularly preferably 1 mol % or less, relative to the total number of moles including other structural portions.
[0028] The physical properties of the PAS resin are not particularly limited as long as they do not impair the effects of the present invention, but are as follows.
[0029] (Melt Viscosity) The melt viscosity of the PAS resin used in the present disclosure is not particularly limited, but in order to obtain a good balance between fluidity and mechanical strength, the melt viscosity (V6) measured at 300°C is preferably in the range of 5 Pa·s or more, more preferably 10 Pa·s or more, and preferably in the range of 45 Pa·s or less, more preferably 40 Pa·s or less. However, the melt viscosity (V6) is measured by using a Shimadzu flow tester, CFT-500D, at 300°C, load: 1.96×10 6 The melt viscosity is measured after holding the sample for 6 minutes at a pressure of 1 Pa and L / D = 10 (mm) / 1 (mm).
[0030] (Non-Newtonian Exponents) The non-Newtonian index of the PAS resin used in the present disclosure is not particularly limited, but is preferably in the range of 0.90 or more to 2.00 or less. When a linear PAS resin is used, the non-Newtonian index is preferably in the range of 0.90 or more, more preferably 0.95 or more, and preferably 1.50 or less, more preferably 1.20 or less. Such a PAS resin is excellent in mechanical properties, fluidity, and abrasion resistance. However, in the present disclosure, the non-Newtonian index (N value) is a value calculated using the following formula by measuring the shear rate (SR) and shear stress (SS) using a capillary rheometer under the conditions of a melting point of +20°C and a ratio of the orifice length (L) to the orifice diameter (D) of L / D=40. The closer the non-Newtonian index (N value) is to 1, the closer the structure is to a linear structure, and the higher the non-Newtonian index (N value), the more branched the structure is.
[0031]
number
[0032] (Manufacturing method) The method for producing the PAS resin is not particularly limited, but examples thereof include (production method 1) a method in which a dihalogeno aromatic compound is polymerized in the presence of sulfur and sodium carbonate, and if necessary, a polyhalogeno aromatic compound or other copolymerization component is added, (production method 2) a method in which a dihalogeno aromatic compound is polymerized in a polar solvent in the presence of a sulfidizing agent or the like, and if necessary, a polyhalogeno aromatic compound or other copolymerization component is added, (production method 3) a method in which p-chlorothiophenol is added, and if necessary, other copolymerization components are added, and self-condensation is performed, and (production method 4) a method in which a diiodo aromatic compound and elemental sulfur are melt-polymerized under reduced pressure in the presence of a polymerization inhibitor that may have a functional group such as a carboxy group or an amino group. Among these methods, (production method 2) is preferred because it is versatile. During the reaction, an alkali metal salt of a carboxylic acid or sulfonic acid or an alkali hydroxide may be added to adjust the degree of polymerization. Among the above-mentioned (Production Method 2) methods, there is a method for producing a PAS resin by introducing a water-containing sulfidizing agent into a mixture containing a heated organic polar solvent and a dihalogeno aromatic compound at a rate at which water can be removed from the reaction mixture, and then reacting the dihalogeno aromatic compound and the sulfidizing agent in the organic polar solvent, and optionally adding a polyhalogeno aromatic compound, and controlling the amount of water in the reaction system to within a range of 0.02 to 0.5 mol per mol of the organic polar solvent (see JP-A-07-228699). Particularly preferred is a method in which a dihalogeno-aromatic compound and, if necessary, a polyhalogeno-aromatic compound or other copolymerization component are added in the presence of potassium metal sulfide and an aprotic polar organic solvent, and an alkali metal hydrosulfide and an organic acid alkali metal salt are reacted while controlling the organic acid alkali metal salt in the range of 0.01 to 0.9 mol per mol of the sulfur source and the amount of water in the reaction system to 0.02 mol or less per mol of the aprotic polar organic solvent (see WO2010 / 058713 pamphlet).Specific examples of the dihalogenoaromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-di Examples of the polyhalogeno aromatic compounds include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, 1,4,6-trihalonaphthalene, etc. The halogen atoms contained in the above compounds are preferably chlorine atoms or bromine atoms.
[0033] The method for post-treating the reaction mixture containing the PAS resin obtained by the polymerization step is not particularly limited, but for example, (post-treating 1) after the completion of the polymerization reaction, first, the solvent is distilled off under reduced pressure or normal pressure, either as is or after adding an acid or base, and then the solid matter remaining after the solvent distillation is washed once or twice or more times with a solvent such as water, the reaction solvent (or an organic solvent having a similar solubility to the low molecular weight polymer), acetone, methyl ethyl ketone, or alcohols, and then neutralized, washed with water, filtered, and dried; or (post-treating 2) after the completion of the polymerization reaction, the reaction mixture is dissolved in a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, or aliphatic hydrocarbons (soluble in the polymerization solvent used and poorly soluble in at least PAS). or (post-treatment 3) after the polymerization reaction is completed, a reaction solvent (or an organic solvent having a solubility equivalent to that of the low molecular weight polymer) is added to the reaction mixture, the mixture is stirred, the mixture is filtered to remove the low molecular weight polymer, the mixture is washed once or twice or more times with a solvent such as water, acetone, methyl ethyl ketone, or an alcohol, and then the mixture is neutralized, washed with water, filtered, and dried; (post-treatment 4) after the polymerization reaction is completed, water is added to the reaction mixture, the mixture is washed with water, filtered, and if necessary, an acid is added during the water washing to perform an acid treatment, and then the mixture is dried; or (post-treatment 5) after the polymerization reaction is completed, the reaction mixture is filtered, and if necessary, the mixture is washed once or twice or more times with the reaction solvent, and then the mixture is washed with water, filtered, and dried.
[0034] In the post-treatment methods exemplified above in (Post-treatment 1) to (Post-treatment 5), the PAS resin may be dried in a vacuum, or in air or in an inert gas atmosphere such as nitrogen.
[0035] In addition, the PAS resin used in this embodiment may be a PAS resin newly polymerized by the above method, or a recycled PAS resin. For example, a PAS resin recovered from a PAS resin composition or a PAS resin molded product may be used. Specifically, a PAS resin obtained by heating a PAS resin composition or a PAS resin molded product in an organic polar solvent to dissolve the PAS resin contained therein and performing the above-mentioned post-treatment on the solution may be used. In addition, a PAS resin composition or a PAS resin molded product mechanically crushed may be used as the PAS resin. Specifically, a sprue or runner generated during the manufacture of a molded product, a product recovered as a non-standard molded product, or a molded product once used as a product may be crushed. In this case, a crushed product of a PAS resin composition or a PAS resin molded product containing a component other than the PAS resin may be used.
[0036] The amount of PAS resin in the PAS resin composition according to this embodiment is not particularly limited as long as it does not impair the effects of the present invention, but is preferably in the range of 20 parts by mass or more, more preferably 25 parts by mass or more, and even more preferably 30 parts by mass or more, relative to 100 parts by mass of the resin composition, and is preferably in the range of 55 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 45 parts by mass or less. Within such a range, the resin composition exhibits good mechanical properties, which is preferable.
[0037] -Non-fibrous filler with thermal conductivity of 15 W / m K or more In addition to the above components, the resin member according to this embodiment may contain a non-fibrous filler as an optional component for the purpose of further improving the thermal conductivity, as long as the effect of the present invention is not impaired. The non-fibrous filler applicable to this embodiment may have a thermal conductivity of 15 W / m·K or more, and any known material may be used as long as it does not impair the effect of the present invention. For example, carbon-based materials such as graphene and graphite, boron nitride, aluminum nitride, aluminum oxide, magnesium oxide, zinc oxide, magnesium carbonate, silicon carbide, boehmite, metal powder, etc. may be used.
[0038] The compounding amount of the non-fibrous filler is preferably 85 parts by mass or more, more preferably 100 parts by mass or more, based on 100 parts by mass of the PAS resin. Further, it is preferably 210 parts by mass or less, more preferably 200 parts by mass or less. In such a range, the resin composition and the molded product are excellent in the balance between heat dissipation and weld strength.
[0039] The average particle diameter (D 50 ) of the non-fibrous filler is preferably in the range of 45 μm or less, more preferably 20 μm or less, from the viewpoint of excellent surface smoothness. The average particle diameter (D 50 ) of the non-fibrous filler is the average particle diameter (D 50 ) determined based on the particle size distribution measured according to a conventional method using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII).
[0040] The roundness (R) of the non-fibrous filler is preferably in the range of 0.50 or more, more preferably in the range of 0.60 or more, from the viewpoint of excellent surface smoothness. The roundness (R) of the magnesium carbonate is a parameter calculated by the following formula. Roundness (R) = 4πS / L 2 In the above formula, S and L are the measured values (S) of the two-dimensional projected area and the perimeter (L) of magnesium carbonate measured using an image processing software (automatic area measurement attached to the Keyence digital microscope VHX-6000) by photographing a projected image of magnesium carbonate at a magnification (200 times) with a microscope (Keyence microscope VHX-6000). The roundness referred to in the present invention is the number average value calculated from the measurement results of the projected area (S) and the perimeter (L) of 50 to 100 magnesium carbonates photographed in a single projected image. The roundness (R) is greater than 0 and 1 or less (0 < R ≤ 1). If it has a perfect spherical shape and the above projected image is a perfect circle, the roundness (R) = 1.
[0041] · Fibrous filler In addition to the above components, the resin member according to the present embodiment may contain fibrous fillers as optional components for the purpose of further improving the mechanical strength, within a range that does not impair the effects of the present invention. As these fibrous fillers, any known or commonly used material may be used as long as it does not impair the effects of the present invention, and examples of such fibrous fillers include glass fiber, carbon fiber, silane glass fiber, ceramic fiber, wollastonite fiber, aramid fiber, and metal fiber.
[0042] When a fibrous filler is blended, the blending amount is preferably 90 parts by mass or less, more preferably 80 parts by mass or less, based on 100 parts by mass of the PAS resin. In this range, a molded product having better mechanical properties can be obtained. In addition, from the viewpoint of the resin member having good weld strength, the blending amount is preferably 25 parts by mass or more, more preferably 30 parts by mass or more.
[0043] ·Optional ingredients
[0044] The PAS resin composition according to this embodiment may contain a non-fibrous filler having a thermal conductivity of 15 W / m·K or less as an optional component for the purpose of improving mechanical strength, within a range that does not impair the effects of the present invention. Examples of the filler include fillers of various shapes, such as plate-like and spherical. Specifically, non-fibrous fillers such as glass beads, glass flakes, calcium carbonate, magnesium carbonate, calcium sulfate, barium sulfate, clay, pyrophyllite, bentonite, sericite, mica, talc, attapulgite, ferrite, calcium silicate, zeolite, wollastonite, and boehmite can be used.
[0045] In the present disclosure, the non-fibrous filler is not an essential component, but when it is blended, the blending amount is not particularly limited as long as it does not impair the effects of the present invention. The blending amount of the other filler is, for example, preferably 1 part by mass or more, more preferably 5 parts by mass or more, and preferably 600 parts by mass or less, more preferably 200 parts by mass or less, relative to 100 parts by mass of the PAS resin. In such a range, the resin composition exhibits good moldability and the molded product has excellent mechanical properties, which is preferable.
[0046] The PAS resin composition according to the present embodiment can be blended with a silane coupling agent as an optional component as necessary. The PAS resin silane coupling agent of the present disclosure is not particularly limited as long as it does not impair the effects of the present invention, but a silane coupling agent having a functional group that reacts with a carboxy group, such as an epoxy group, an isocyanato group, an amino group or a hydroxyl group, is preferably mentioned. Examples of such silane coupling agents include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane. In this embodiment, the silane coupling agent is not an essential component, but when it is added, the amount of the silane coupling agent is not particularly limited as long as it does not impair the effects of the present invention, and is preferably in the range of 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, to preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the PAS resin. In this range, the resin composition has good corona resistance and moldability, especially releasability, and the molded product exhibits excellent adhesion to the epoxy resin while further improving mechanical strength, which is preferable.
[0047] The PAS resin composition according to the present embodiment may contain a thermoplastic elastomer as an optional component, if necessary. Examples of the thermoplastic elastomer include polyolefin elastomers, fluorine elastomers, and silicone elastomers, among which polyolefin elastomers are preferred. When these elastomers are added, the amount of the elastomers is not particularly limited as long as it does not impair the effects of the present invention, but is preferably in the range of 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, to preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the PAS resin. In this range, the impact resistance of the resulting PAS resin composition is improved, which is preferable.
[0048] For example, the polyolefin-based elastomer may be a homopolymer of an α-olefin, a copolymer of two or more α-olefins, or a copolymer of one or more α-olefins and a vinyl polymerizable compound having a functional group. In this case, the α-olefin may be an α-olefin having 2 or more to 8 or less carbon atoms, such as ethylene, propylene, or 1-butene. In addition, the functional group may be a carboxy group, an acid anhydride group (-C(=O)OC(=O)-), an epoxy group, an amino group, a hydroxyl group, a mercapto group, an isocyanate group, or an oxazoline group. Examples of the vinyl polymerizable compound having the functional group include one or more of vinyl acetate, α,β-unsaturated carboxylic acids such as (meth)acrylic acid, alkyl esters of α,β-unsaturated carboxylic acids such as methyl acrylate, ethyl acrylate, and butyl acrylate, metal salts of α,β-unsaturated carboxylic acids such as ionomers (metals include alkali metals such as sodium, alkaline earth metals such as calcium, and zinc), glycidyl esters of α,β-unsaturated carboxylic acids such as glycidyl methacrylate, and the like, α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid, and derivatives of the α,β-unsaturated dicarboxylic acids (monoesters, diesters, and acid anhydrides). The above-mentioned thermoplastic elastomers may be used alone or in combination of two or more.
[0049] Furthermore, in addition to the above components, the PAS resin composition according to the present embodiment may further contain synthetic resins such as polyester resin, polyamide resin, polyimide resin, polyetherimide resin, polycarbonate resin, polyphenylene ether resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylene resin, polyethylene resin, polypropylene resin, polytetrafluoroethylene resin, polydifluoroethylene resin, polystyrene resin, ABS resin, epoxy resin, phenol resin, urethane resin, and liquid crystal polymer as optional components depending on the application. In particular, it is preferable to add a fluorine-based resin because it improves the sliding properties. In the present disclosure, the synthetic resin is not an essential component, but when it is added, the ratio of the synthetic resin is not particularly limited as long as it does not impair the effects of the present invention, and it differs depending on each purpose and cannot be generally defined, but the ratio of the synthetic resin to be added in the resin composition according to the present disclosure is, for example, in the range of 5 parts by mass or more and 15 parts by mass or less relative to 100 parts by mass of PAS resin. In other words, the ratio of the PAS resin to the total of the PAS resin and the synthetic resin is preferably in the range of (100 / 115) or more, and more preferably in the range of (100 / 105) or more, based on mass.
[0050] In addition, the PAS resin composition according to the present embodiment may contain other known and commonly used additives as optional components, such as colorants, antistatic agents, antioxidants, heat stabilizers, UV stabilizers, UV absorbers, foaming agents, flame retardants, flame retardant assistants, rust inhibitors, and release agents (metal salts or esters of fatty acids having 18 to 30 carbon atoms, including stearic acid or montanic acid, polyolefin waxes such as polyethylene, etc.) as needed. These additives are not essential components, and may be used in an amount of, for example, preferably 0.01 parts by mass or more, and preferably 1000 parts by mass or less, more preferably 100 parts by mass or less, based on 100 parts by mass of the PAS resin, depending on the purpose and use so as not to impair the effects of the present invention.
[0051] The PAS resin composition used in this embodiment has a thermal conductivity in the thickness direction of 0.65 W / m·K or more. More preferably, it is more than 0.65 W / m·K, and more preferably 0.70 W / m·K or more. In order to set the thermal conductivity in the thickness direction of the resin composition within this range, it can be achieved by adjusting the thermal conductivity and the amount of the non-fibrous filler to be blended. More specifically, for example, excellent thermal conductivity can be achieved by blending 85 parts by mass or more of a filler with a thermal conductivity of about 30 W / m·K, such as magnesium carbonate, with respect to 100 parts by mass of the resin. In this range, the resin composition has good fluidity during melt kneading and molding processing, and a molded product with excellent appearance can be obtained. The thermal conductivity in the thickness direction in this disclosure is a value measured in the thickness direction of the molded product by the method described in the examples in accordance with JIS R 1611 "Method of measuring thermal diffusivity, specific heat capacity, and thermal conductivity of fine ceramics by flash method".
[0052] The PAS resin composition used in this embodiment preferably has a weld strength of 40 MPa or more. More preferably, it is 45 MPa or more, and even more preferably 50 MPa or more. In this range, the mechanical strength is excellent when the resin member is a molded product having an opening or an insert molded product such as a metal nut. In order to set the weld strength in this range, for example, a method of adjusting the melt viscosity (V6) of the PAS resin within a range of 50 to 2000 Pa·s depending on the content of the PAS resin in the resin composition, or a method of controlling the crystallization behavior of the PAS resin can be mentioned. For example, when a large amount of inorganic filler is blended as a component other than the PAS resin, the crystallization rate of the resin composition tends to increase, so the melt viscosity of the PAS resin can be increased to adjust the crystallization behavior. The method of adjusting the weld strength is not limited to the above-mentioned method. The weld strength in this disclosure refers to the tensile strength of a weld in ISO 527-1,2 of a molded product in which molten resin is filled symmetrically from both ends of a dumbbell-shaped test piece conforming to Type A test piece specified in ISO 20753, and can be measured by the method described in the examples.
[0053] [Method of manufacturing PAS resin composition] The method for producing a PAS resin composition used in a resin member includes a step of blending the above essential components and melt-kneading them at a temperature range equal to or higher than the melting point of the PAS resin. More specifically, the PAS resin composition according to this embodiment is composed of each essential component and, if necessary, other optional components. The method for producing the resin composition used in the present disclosure is not particularly limited, but examples thereof include a method of blending the essential components and, if necessary, optional components, and melt-kneading them, and more specifically, a method of uniformly dry-mixing them in a tumbler or Henschel mixer, if necessary, and then feeding them into a twin-screw extruder to melt-knead them.
[0054] The melt kneading can be carried out by heating the resin to a temperature range in which the resin temperature is equal to or higher than the melting point of the PAS resin, preferably equal to or higher than the melting point + 10°C, more preferably equal to or higher than the melting point + 10°C, even more preferably equal to or higher than the melting point + 20°C, preferably equal to or lower than the melting point + 100°C, more preferably equal to or lower than the melting point + 50°C.
[0055] The melt kneader is preferably a twin-screw kneading extruder from the viewpoint of dispersibility and productivity. For example, it is preferable to melt knead while appropriately adjusting the resin component discharge amount in the range of 5 to 500 (kg / hr) and the screw rotation speed in the range of 50 to 500 (rpm), and it is more preferable to melt knead under the condition that the ratio (discharge amount / screw rotation speed) is in the range of 0.02 to 5 (kg / hr / rpm). In addition, each component may be added and mixed to the melt kneader simultaneously or in portions. For example, when graphite (B), which is an essential component, or other fibrous fillers are added as necessary among the components, it is preferable to feed them into the extruder from a side feeder of the twin-screw kneading extruder from the viewpoint of dispersibility. The position of the side feeder is preferably such that the ratio of the distance from the extruder resin input part (top feeder) to the side feeder to the total screw length of the twin-screw kneading extruder is 0.1 or more, more preferably 0.3 or more. Moreover, the ratio is preferably 0.9 or less, and more preferably 0.7 or less.
[0056] The PAS resin composition according to the present disclosure obtained by melt kneading in this manner is a molten mixture containing the essential components, optional components added as necessary, and components derived therefrom. Therefore, the PAS resin composition according to the present disclosure has a morphology in which the PAS resin forms a continuous phase and other essential components and optional components are dispersed. After the melt kneading, the PAS resin composition according to the present disclosure is preferably pre-dried at a temperature range of 100 to 150°C by a known method, for example, by extruding the molten resin composition into a strand shape, and then processing it into a form such as pellets, chips, granules, or powder.
[0057] [PAS resin molded products and manufacturing methods for PAS resin molded products] Next, a molded product, which is one of the components of the resin member, will be described. The molded product used in this embodiment is obtained by melt molding the PAS resin composition. The manufacturing method of the molded product used in this embodiment includes a step of melt molding the PAS resin composition. Therefore, the molded product according to this embodiment has a morphology in which the PAS resin forms a continuous phase and other essential components and optional components are dispersed. The PAS resin composition has such a morphology, so that a molded product having excellent thermal conductivity and mechanical strength can be obtained. In addition, when the molded product used in this embodiment is melt molded from the PAS resin composition, a member used for joining, such as a nut, may be insert molded.
[0058] In terms of adhesion to a metal member, the resin member made of the PAS resin molded product used in this embodiment has a number average developed area ratio (Sdr) of 0.03% or less when any five points of the resin member are measured using a confocal microscope in accordance with ISO 25178. From the same viewpoint, it is preferably less than 0.015%, more preferably 0.01% or less, and even more preferably 0.005% or less. Within this range, the surface of the resin member is smooth and adheres better when combined with the metal member, so that loss of thermal conduction due to interface thermal resistance due to an air layer can be suppressed.
[0059] From the viewpoint of adhesion to a metal member, the resin member made of the PAS resin molded product used in this embodiment preferably has a surface roughness Rz of 3.0 μm or less, more preferably less than 3.0 μm, and even more preferably 2.8 μm or less. The surface roughness Rz of the resin member can be measured by the method described in the examples in accordance with JIS-B 0601-2001 (ISO4287).
[0060] The resin member made of the PAS resin molded product used in this embodiment has a thermal conductivity in the thickness direction of 0.65 W / m·K or more. Also, 0.7 W / m·K or more is preferable, and 1.0 W / m·K or more is more preferable. In this range, the composite structure has excellent heat dissipation properties. The thermal conductivity in the thickness direction of the resin member can be measured by the method described in the examples in accordance with JIS R 1611 "Method for measuring thermal diffusivity, specific heat capacity, and thermal conductivity of fine ceramics by the flash method."
[0061] The PAS resin composition used in this embodiment can be subjected to various molding processes such as injection molding, compression molding, extrusion molding of composites, sheets, pipes, etc., pultrusion molding, blow molding, and transfer molding, but is particularly suitable for injection molding applications because it has excellent releasability. When molding by injection molding, various molding conditions are not particularly limited, and molding can be performed by a normal general method. For example, in an injection molding machine, the PAS resin composition is melted at a resin temperature in a temperature range of the melting point of the PAS resin or higher, preferably in a temperature range of the melting point + 10°C or higher, more preferably in a temperature range of the melting point + 10°C to the melting point + 100°C, and even more preferably in a temperature range of the melting point + 20 to the melting point + 50°C, and then the resin is injected into a mold from a resin discharge port and molded. At that time, the mold temperature may also be set to a known temperature range, for example, room temperature (23°C) to 300°C, preferably 130 to 190°C.
[0062] The method for producing a PAS resin molded article used in this embodiment may include a step of annealing the molded article. The optimum conditions for the annealing treatment are selected depending on the application or shape of the molded article, and the annealing temperature is in a temperature range equal to or higher than the glass transition temperature of the PAS resin, preferably in a temperature range equal to or higher than the glass transition temperature +10°C, and more preferably in a temperature range equal to or higher than the glass transition temperature +30°C. On the other hand, it is preferably in a range of 260°C or lower, and more preferably in a range of 240°C or lower. The annealing time is not particularly limited, but is preferably in a range of 0.5 hours or higher, and more preferably in a range of 1 hour or higher. On the other hand, it is preferably in a range of 10 hours or lower, and more preferably in a range of 8 hours or lower. In such a range, not only the distortion of the molded article obtained is reduced and the crystallinity of the resin is improved, but also the thermal conductivity, mechanical properties, and fuel barrier properties are further improved, which is preferable. The annealing treatment may be performed in air, but is preferably performed in an inert gas such as nitrogen gas.
[0063] The PAS resin molded product used in this embodiment includes a remolded product obtained by reusing a molded product obtained by melt molding the PAS resin composition. Specifically, for example, it includes a sprue or runner generated during the manufacture of a molded product, a molded product recovered as a non-standard molded product, or a molded product once used as a product, which is washed as necessary, crushed, and melt molded again at a temperature equal to or higher than the melting point of the PAS resin. When reusing, it is preferable to mix the crushed molded product with the PAS resin composition from the viewpoint of mechanical properties. The size of the molded product when crushed is not particularly limited, but it is preferable that the size is about the same as that of the PAS resin composition to be mixed from the viewpoint of mixability and processability. In addition, the mixing ratio is preferably 50 parts by mass or less of the crushed molded product relative to 100 parts by mass of the PAS resin composition, more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less. Within this range, the recyclability can be improved without impairing the effects of the PAS resin composition of the present disclosure.
[0064] <Method of manufacturing composite structure> The method for producing a composite structure disclosed herein includes a step of joining a metal member and a resin member consisting of a molded product obtained by melt-molding a PAS resin composition containing a PAS resin, wherein the resin composition has a thermal conductivity in the thickness direction of 0.65 W / m K or more, and the number average developed area ratio (Sdr) of any five points of the resin member is 0.03% or less when measured using a confocal microscope in accordance with ISO 25178.
[0065] As a method for joining the metal member and the resin member, a known joining method or device can be used as long as it does not impair the effects of the present invention. For example, a method of simply stacking the metal member and the resin member, a method of crimping the metal member and the resin member, a method of mechanically joining the metal member and the resin member, etc. Specific methods for mechanically joining the metal member and the resin member include, for example, a method of mechanically fastening the metal member and the resin member using screws, rivets, pins, shafts, bolts, nuts, clamps, etc., and fixing with a fitting structure.
[0066] The composite structure of the present disclosure also includes an embodiment in which a resin member is joined to a metal member by plating the resin member. For example, a metal plating layer can be formed on the surface of a resin member made of a PAS resin molded product by electrolytic plating, electroless plating, or a combination of these.
[0067] The electroless plating method is, for example, a method of contacting the surface of the resin member with an electroless plating solution to deposit metals such as copper contained in the electroless plating solution and form an electroless plating layer (film) made of a metal film. The electrolytic plating method is, for example, a method of applying electricity to the surface of the electroless plating layer (film) formed by the electroless plating process while the electrolytic plating solution is in contact with the surface of the electroless plating layer (film) formed by the electroless plating process, to deposit metals such as copper contained in the electrolytic plating solution on the surface of the electroless plating layer (film) formed by the electroless process placed at the cathode, thereby forming an electrolytic plating layer (metal film).
[0068] The composite structure of the present disclosure is characterized by excellent mold transferability and thermal conductivity, and is therefore particularly suitable for use as a member (heat dissipation member) that efficiently conducts and dissipates heat. Specifically, it can be suitably used as a heat dissipation member for use in a vehicle, such as a heat exchanger, a heat dissipation plate, or a cooling fin, or as a heat dissipation member for electronic components. The composite structure of the present disclosure can be used not only as a heat dissipation member, but also as a normal resin molded product such as the following. For example, a protective / support member for a box-shaped electric / electronic component integrated module, a plurality of individual semiconductors or modules, a sensor, an LED lamp, a connector, a socket, a resistor, a relay case, a switch, a coil bobbin, a capacitor, a variable capacitor case, an optical pickup, an oscillator, various terminal boards, a transformer, a plug, a printed circuit board, a tuner, a speaker, a microphone, a headphone, a small motor, a magnetic head base, a power module, a terminal block, a semiconductor, a liquid crystal, an FDD carriage, an FDD chassis, a motor brush holder, a parabolic antenna, an electric / electronic component represented by computer-related components, a VTR component, a television component, an iron, a headphone ... Home and office electrical appliance parts such as air dryers, rice cooker parts, microwave oven parts, audio parts, audio / visual equipment parts such as laser discs, compact discs, DVD discs, and Blu-ray discs, lighting parts, refrigerator parts, air conditioner parts, typewriter parts, word processor parts, and water-related equipment parts such as water heaters, bath water volume and temperature sensors; office computer related parts, telephone related parts, facsimile related parts, copier related parts, cleaning jigs, motor parts, lighters, typewriters, and other machine related parts; optical equipment and precision machinery related parts such as microscopes, binoculars, cameras, and watches;Alternator terminals, alternator connectors, brush holders, slip rings, IC regulators, potentiometer bases for light dimmers, relay blocks, inhibitor switches, various valves such as exhaust gas valves, various pipes for fuel, exhaust and intake systems, air intake nozzle snorkels, intake manifolds, engine coolant joints, carburetor main bodies, carburetor spacers, exhaust gas sensors, coolant sensors, oil temperature sensors, brake pad wear sensors, throttle position sensors, crankshaft position sensors, temperature sensors, air flow meters, brake pad wear sensors, thermostat bases for air conditioners, heating hot air flow control valves, radiators Examples of automotive and vehicle related parts include brush holders for motors, water pump impellers, turbine vanes, wiper motor related parts, distributors, starter switches, ignition coils and bobbins, motor insulators, motor rotors, motor cores, starter relays, transmission wire harnesses, windshield washer nozzles, air conditioner panel switch boards, coils for fuel-related electromagnetic valves, fuse connectors, horn terminals, electrical component insulating plates, step motor rotors, lamp sockets, lamp reflectors, lamp housings, brake pistons, solenoid bobbins, engine oil filters, ignition device cases, and other various applications. EXAMPLES
[0069] Hereinafter, the present disclosure will be described using examples and comparative examples, but is not limited to these examples. In the following, unless otherwise specified, "%" and "parts" are based on mass.
[0070] <Examples 1 to 5 and Comparative Examples 1 to 2> Each material was mixed according to the composition and mixing amount shown in Table 1. Then, these mixed materials were fed into a vented twin screw extruder "TEX-30α (product name)" manufactured by Japan Steel Works, Ltd., and melt-kneaded at a resin component discharge rate of 25 kg / hr, a screw rotation speed of 200 rpm, and a set resin temperature of 330°C to obtain pellets of the resin composition. The raw material components were mixed uniformly in a tumbler beforehand and fed from the top feeder. The obtained pellets of the resin composition were dried for 2 hours in a gear oven at 140°C, and then injection molded to produce each resin part. As the metal part, a SUS304 plate (width 60 mm, length 60 mm, thickness 10 mm) with a surface roughness of Rz2.1 μm was used.
[0071] <Evaluation>
[0072] (1) Measurement of thermal conductivity (xenon flash method) Pellets of the resin composition obtained in each Example and Comparative Example were fed to a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set at 310°C, and injection molding was performed using a mold for ISO D2 sheet molding with a mold temperature controlled at 140°C to obtain an ISO D2 sheet. The obtained ISO D2 sheet was cut into a size of 10 mm x 10 mm x 2 mmt to prepare a test piece, and the thermal conductivity (W / m·K) was measured in the thickness direction of the molded product in accordance with JIS R 1611 "Method of measuring thermal diffusivity, specific heat capacity, and thermal conductivity of fine ceramics by flash method". The measurement results are shown in Table 1.
[0073] (2) Measurement of Sdr (surface roughness) of resin parts The ISO D2 sheet obtained in the same manner as in (1) was used as a test piece, and the surface roughness was evaluated using a confocal microscope (manufactured by Lasertec, OPTELICS HYBRID) in accordance with a method conforming to ISO25178. A white light source was used, and the confocal mode was used. As the objective lens, one with a magnification in which one side of the field of view range was 2 to 10 times the average length (RSm) of the roughness curve element obtained in Measurement Example 2 was selected. The scanning resolution in the height direction was set to 10 nm, and an original surface image of the three-dimensional height of the test piece surface was obtained in search peak mode. After performing surface tilt correction on the original surface image, surface filtering was performed with an S filter of 2.5 μm and an L filter of 0.8 μm (both Gaussian filters), and the entire image obtained by applying a median filter (filter size 3 × 3) for noise reduction once was used as the evaluation area, and the developed area ratio (Sdr) of the test piece was obtained. The measurement points were the center of the surface of the obtained molded product that contacted the movable side mold during injection molding, and five points at the square, and the Sdr value obtained by averaging the values at the five points was used. The measurement results are shown in Table 1.
[0074] (3) Rz (surface roughness) measurement of resin and metal parts The surface roughness of the ISO D2 sheet obtained in the same manner as in (1) and the metal member was evaluated in accordance with JIS-B 0601-2001 (ISO4287) using a stylus-type surface roughness tester (Tokyo Seimitsu, Surfcom 1400D). A spherical indenter (tip radius 2 μm) was used, and the evaluation length was 4 mm, the scanning speed was 0.06 mm / s, the reference length was 0.8 mm, the low-pass cutoff length was 2.5 μm, and the roughness curve was obtained using a Gaussian function as the cutoff filter. The measurement points were two arbitrary straight lines in a parallel relationship on the surface of each member, and two arbitrary straight lines in a perpendicular relationship to these, and the average value of the above parameters for a total of four straight lines was used. The measurement results are shown in Table 1.
[0075] (4) Evaluation of tensile strength Pellets of the resin composition obtained in each Example and Comparative Example were fed to a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set to 310°C, and injection molding was performed using an ISO Type 1A dumbbell piece molding die with a mold temperature controlled to 140°C to obtain an ISO Type-A dumbbell piece. The resin was injected from two gates at both ends to produce a test piece including a weld. The tensile strength of the obtained dumbbell piece was measured using a measurement method based on ISO 527-1 and 2. The measurement results are shown in Table 1.
[0076] (5) Heat dissipation evaluation of composite structures A stainless steel plate (E-1 component in Table 1) with a width of 60 mm, length of 60 mm, and thickness of 10 mm was sufficiently heated to 150°C on a heater, and then the ISO D2 sheet of each resin composition prepared in the same manner as in (1) was placed on the stainless steel plate to form a composite structure, and heating was stopped at the same time. Before the placement, a thermocouple was attached with Kapton tape to the center of the surface of the ISO D2 sheet that was not in contact with the stainless steel plate, so that the surface temperature of the resin composition could be measured. The time of placement was set to 0 seconds, and the surface temperature of the ISO D2 sheet was measured after 1 minute. The measurement results are shown in Table 1. A higher temperature indicates better heat dissipation.
[0077] [Table 1]
[0078] The blending ratios of the blended components in Table 1 are as follows: A-1: PPS resin, linear type, melt viscosity (V6) 8 Pa·s B-1: Magnesium carbonate "Magthermo MS-PS" manufactured by Konoshima Chemical Co., Ltd. (D 50 = 10.6 μm, circularity 0.83, maximum particle size 44 μm), thermal conductivity 30 W / m K B-2: Magnesium carbonate "magnesite fine powder" manufactured by Sobueclair Co., Ltd. was filtered under pressure using a 120 mesh (capture particle diameter of more than 125 μm) filter to remove the captured particles, and particles were obtained (D 50= 17.9 μm, circularity 0.68), thermal conductivity 30 W / m K C-1: Glass fiber, product name "T-731H", manufactured by Nippon Electric Glass Co., Ltd., fiber length 3 mm, average diameter 10 μm C-2: Carbon fiber, product name "Dialead K223HE", manufactured by Mitsubishi Chemical Corporation, fiber length 6 mm, average diameter 11 μm D-1: Thermoplastic elastomer, product name "BondFast-7L", manufactured by Sumitomo Chemical Co., Ltd. E-1: Stainless steel plate SUS304, surface roughness Rz2.1μm
[0079] Table 1 shows that in Comparative Examples 1 and 2 in which the resin member does not satisfy the conditions of thermal conductivity and / or development area ratio, the heat dissipation of the composite is poor compared to the Examples.
Claims
1. A composite structure formed by bonding a metal member and a resin member made of a molded product obtained by melt molding a polyarylene sulfide resin composition containing a polyarylene sulfide resin, The thermal conductivity of the resin composition in the thickness direction is 0.65 W / m K or more, and A composite structure, wherein the resin member has a number average developed area ratio (Sdr) of 0.03% or less when any five points on the resin member are measured using a confocal microscope in accordance with ISO 25178.
2. 2. The composite structure according to claim 1, wherein the resin member has a surface roughness Rz of 3.0 [mu]m or less.
3. 3. The composite structure according to claim 1, wherein the resin composition is a mixture of a polyarylene sulfide resin, a fibrous filler, and a non-fibrous filler having a thermal conductivity of 15 W / m·K or more.
4. 4. The composite structure according to claim 3, wherein the amount of the fibrous filler in the resin composition is in the range of 25 to 90 parts by mass per 100 parts by mass of the polyarylene sulfide resin.
5. The composite structure according to claim 3, wherein the amount of the non-fibrous filler having a thermal conductivity of 15 W / m·K or more in the resin composition is in the range of 85 to 200 parts by mass per 100 parts by mass of the polyarylene sulfide resin.
6. The composite structure according to claim 1 or 2, wherein the resin composition has a weld strength of 40 MPa or more. (Note that the weld strength is the tensile strength at the weld, measured in accordance with ISO 527-1 and 2, using a molded product in which molten resin is filled symmetrically from both ends of a dumbbell-shaped test piece conforming to the Type A test piece specified in ISO 20753.)
7. 3. The composite structure according to claim 1, wherein the metal member is at least one selected from the group consisting of aluminum, copper, magnesium, iron, titanium, and alloys containing any of these.
8. 3. The composite structure according to claim 1, wherein the surface roughness Rz of the metal member is 3.0 μm or less.
9. A method for producing a composite structure, comprising a step of joining a metal member and a resin member made of a molded product obtained by melt molding a polyarylene sulfide resin composition containing a polyarylene sulfide resin, The thermal conductivity of the resin composition in the thickness direction is 0.65 W / m K or more, and a number average developed area ratio (Sdr) of 0.03% or less when any five points of the resin member are measured in accordance with ISO 25178 using a confocal microscope.
10. The method for producing a composite structure according to claim 9 , wherein the resin member has a surface roughness Rz of 3.0 μm or less.
11. The method for producing a composite structure according to claim 9 or 10, wherein the resin composition is a blend of a polyarylene sulfide resin, a fibrous filler, and a non-fibrous filler having a thermal conductivity of 15 W / m·K or more.
12. The method for producing a composite structure according to claim 11, wherein the amount of the fibrous filler in the resin composition is in the range of 25 to 90 parts by mass per 100 parts by mass of the polyarylene sulfide resin.
13. The composite structure according to claim 11, wherein the amount of the non-fibrous filler having a thermal conductivity of 15 W / m·K or more in the resin composition is in the range of 85 to 200 parts by mass per 100 parts by mass of the polyarylene sulfide resin.
14. The method for producing a composite structure according to claim 9 or 10, wherein the resin composition has a weld strength of 40 MPa or more. (Note that the weld strength is the tensile strength at the weld, measured in accordance with ISO 527-1 and 2, using a molded product in which molten resin is filled symmetrically from both ends of a dumbbell-shaped test piece conforming to the Type A test piece specified in ISO 20753.)
15. The method for producing a composite structure according to claim 9 or 10, wherein the metal member is at least one selected from the group consisting of aluminum, copper, magnesium, iron, titanium, and alloys containing any of them.
16. The method for producing a composite structure according to claim 9 or 10, wherein the surface roughness Rz of the metal member is 3.0 μm or less.
Citation Information
Patent Citations
Resin composition, molded article and optical pickup base for recording
JP2004339290A
Resin composition, its molding and method for producing resin composition
JP2022160098A
Resin composition having high thermal conductivity
WO2013161844A1